Pengaruh Jam Kerja Orang Tua terhadap Kognitif Anak di Indonesia - Gemellia, Pradini Ajeng; Wongkaren, Turro S. (UI Scholars Hub, 2021)
The current phenomenon shows an increasing work activities by both fathers and mothers to fulfil household needs. This social change is feared to give children imbalance time, causing children’s development to be not optimal. This study aims to see the influence of parental working hour on children’s cognitive scores in Indonesia. This study used data from IFLS Survey in 2007 and 2014 with a unit of analysis of children aged 7 to 14 used an OLS estimation method. The results of this study indicate that parental working hours had negative influence on children’s cognitive scores.